(untitled) (Research, Society and Development, 2022)
The new Coronavirus pandemic (COVID-19) brought with it several changes that impacted society, from the way we structure our social relationships, through work interactions and directly affecting the way we communicate, and consequently, the current learning models. Therefore, the present work aims to make an exploratory bibliographic study - performing a result mining work from a database with more than 20,000 (twenty thousand) respondents. The database under analysis was constituted from the course “Educational Technology, Blended Learning and Pedagogical Innovation” offered by the Digital Educational Laboratory (LDE), of the Federal University of Ceará (UFC), of a continuing education nature - at the level of improvement - promoted during the moment of physical isolation imposed by the pandemic, intended - and with the participation - of education professionals from all over Brazil. It is intended to trace the profile of these professionals who participated in the course, their main initial personal demands, the final knowledge obtained by them, and especially the immediate impacts promoted by the course on the educational practice of the research subjects.